Tafsir Al-Munir by Anregurutta Daud Ismail: A Visionary Scholar from South Sulawesi - Khaerussalam, Ahmad; Resky Eka Yulianti; Mumtazatul Kamilah (Hikami : Jurnal Ilmu Alquran dan Tafsir, 2025)
This study explores the contribution of Daud Ismail to the development of Quranic interpretation in the Bugis language through Tafsir Al-Munir. Using a descriptive-analytical method with a historical-critical approach, the research highlights how Anregurutta Daud Ismail contextualized the ijmali method with an adabi ijtimai style, aligning Quranic messages with Bugis traditions. The findings reveal three distinctive features: (1) the use of the Bugis language and lontarak script as a medium for preserving culture and preaching Islam; (2) the application of a moderate exegetical approach combining bi al-matsur and bi al-ray; and (3) a critical response to religious practices considered to diverge from Islamic teachings. Tafsir Al-Munir reflects a jurisprudential and communal outlook, affirming Daud Ismail’s role as a visionary scholar who connects generations. This study underscores the significance of local-language tafsir in enhancing Quranic understanding and reinforcing an Islamic identity that harmonizes with indigenous values.